Analysis of Sources About the History of Amir Temur and the Temurian Period - Ganiyeva Dilnoza Yuldashali's Qizi (Genius Journals, 2022)
This article analyzes the sources on the history of Amir Temur and the Timurid period. In order to embody the life and activity of Amir Temur, it is important to begin with the most important written sources on which the science of history is based to describe the essence, spirit and environment of his time. The works created during the life of Amir Temur are very valuable as primary sources
Keywords: historian and scholar; Muzaffaris; ethnic